2013
DOI: 10.1128/jb.00637-13
|View full text |Cite
|
Sign up to set email alerts
|

Initiation with Elongator tRNAs

Abstract: In all domains of life, initiator tRNA functions exclusively at the first step of protein synthesis while elongator tRNAs extend the polypeptide chain. Unique features of initiator tRNA enable it to preferentially bind the ribosomal P site and initiate translation. Recently, we showed that the abundance of initiator tRNA also contributes to its specialized role. This motivates the question, can a cell also use elongator tRNA to initiate translation under certain conditions? To address this, we introduced non-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 45 publications
1
35
0
Order By: Relevance
“…E. coli possesses four i-tRNA genes, three at the metZWV locus and the fourth one at the metY locus. Earlier, we showed that deletion of metZWV (encoding ∼75% of total i-tRNA) confers cold sensitivity to E. coli (23)(24)(25). Whereas the ΔmetZWV strain ( Fig.…”
mentioning
confidence: 99%
“…E. coli possesses four i-tRNA genes, three at the metZWV locus and the fourth one at the metY locus. Earlier, we showed that deletion of metZWV (encoding ∼75% of total i-tRNA) confers cold sensitivity to E. coli (23)(24)(25). Whereas the ΔmetZWV strain ( Fig.…”
mentioning
confidence: 99%
“…For example, in our earlier studies, we showed that overproduction of the 3GC mutant tRNA fMet could also lead to a minor increase in initiation, an observation consistent with the role of 3GC base pairs in the direct binding of the tRNA fMet to the 30S ribosome. 42,43 It is also known that an extended SD stabilizes the 70S complex. 52,53 Consistent with this, we observed that kasugamycin treatment (which is known to allow 70S mode of initiation in leaderless mRNAs [54][55][56] ) offered a selective advantage to initiation with the 3GC mutant tRNA fMet from the CAT am1 mRNA with the extended SD sequence.…”
Section: Contribution Of Shine-dalgarno (Sd):anti-sd (Asd) Interactionmentioning
confidence: 96%
“…In the metZWV strain we observed that not only the unusual tRNA fMet of the mycoplasma and rhizobia origin (lacking either the first, the third or both the first and the third GC pairs) but also the elongator tRNAs initiated protein synthesis. 42,43 In fact, initiation by the unusual tRNA fMet sustained growth of E. coli in the absence of all four of the tRNA fMet genes. 27 Normally these unusual tRNAs fail to initiate in E. coli to any significant level.…”
Section: Contribution Of Cellular Initiator Trna Levelsmentioning
confidence: 98%
“…22 Interestingly, none of the trees showed clustering of tRNA i with elongator tRNA Met strongly suggesting against the possibility of them having a close common ancestry. Further, we have previously shown experimentally that the elongator tRNAs can also initiate 37,38 and among them, tRNA Thr , tRNA Pro and tRNA Glu were the most efficient in initiation activity. 38 The logo plot (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we have previously shown experimentally that the elongator tRNAs can also initiate 37,38 and among them, tRNA Thr , tRNA Pro and tRNA Glu were the most efficient in initiation activity. 38 The logo plot (Fig. 4a) shows that the minihelix and the anticodon regions of tRNA i are highly conserved.…”
Section: Discussionmentioning
confidence: 99%